The Influence of Organizational Commitment and Motivation on Employee Performance Through Job Satisfaction (Case Study: Contract Workers at a Power Plant in Pasuruan Regency) - Chandra, Darwis; Pradiani , Theresia; Handoko , Yunus (CV. Tripe Konsultan, 2025)
Generation Business Unit (UBP) Grati, a Gas and Steam Power Plant (PLTGU) located in Pasuruan Regency, East Java, had consistently surpassed its unit performance targets until a notable decline was observed in the first half of 2025. This study aims to investigate the factors contributing to this decline, explicitly focusing on the influence of organizational commitment and motivation on employee performance, with job satisfaction serving as a mediating factor. The research centers on the contract-based workforce (PKWT) at UBP Grati, which constitutes a substantial 47% of the total workforce. Employing a quantitative approach, the study's population consisted of these contract workers, from which a sample of 142 respondents was selected through purposive sampling. Data collection involved questionnaires, interviews, and documentation, with analysis conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.2.9. The findings indicate that organizational commitment and job satisfaction have direct and significant impacts on employee performance. However, motivation does not exhibit a significant direct effect on performance. Notably, the results demonstrate that both organizational commitment and motivation exert important indirect effects on employee performance when mediated by job satisfaction. These findings emphasize the vital role of job satisfaction in transforming both commitment and motivation into enhanced performance for contract workers at UBP Grati.